Randomized controlled trial of early arachidonic acid and docosahexaenoic acid enteral supplementation in very preterm infants - Álvarez, Patricia; Ramiro-Cortijo, David; Montes, María Teresa; Moreno, Bárbara; Calvo, María V.; Liu, Ge; Esteban Romero, Ana; Ybarra, Marta; Cordeiro, Malaika; Clambor Murube, Marina; Valverde, Eva; Sánchez-Pacheco, Aurora; et al. (Frontiers in Pediatrics, 2022)
Objective: To evaluate changes in blood long-chain polyunsaturated fatty acids (LCPUFAs) and oxylipins concentrations in very preterm infants from birth to 36 weeks’ postmenstrual age (WPA) after providing an emulsified arachidonic acid (ARA):docosahexaenoic acid (DHA) supplement at two different concentrations. Study design: This prospective, randomized trial, assigned infants to receive a supplement 1) 80:40 group (80 mg/kg/day ARA and 40 mg/kg/day DHA, n=9); or 2) 120:60 group (120 mg/kg/day ARA and 60 mg/kg/day DHA, n=9). Infants received supplement daily from birth until 36 WPA. At baseline, 21 days of life and 36 WPA, the LCPUFAs were measured in plasma, by gas chromatography/mass spectrophotometry. Additionally, LCPUFAs and oxylipins were analyzed in whole blood by ultra-high performance liquid chromatography-tandem mass spectrometry. Furthermore, a sample of oral mucosa was obtained to analysis single nucleotide polymorphism located in the FADS1 gene by PCR. Results: Gestational age was similar between groups (80:40=28+6 [27+3; 30+3] completed weeks+days; 120:60=29+6 [27+3; 30+5] completed weeks+days, P=0.83). At 36 WPA, the change in plasma ARA were significantly different between groups (80:40 group=0.15 [-0.67; 0.69] %nmol, 120:60=1.68 [1.38; 3.16] %nmol, P=0.031). In whole blood, the levels of ARA-derived oxylipins (5-, 8-, 9-, 11-, 15-HETE and 8,9-EET) and EPA-derived oxylipins (18-HEPE) significantly increase from baseline to 36 WPA in 120:60 group than 80:40 group. Conclusions: Supplementation at high doses (120:60 mg/kg/day) increased levels of ARA, and EPA and ARA derived oxylipins compared to low doses (80:40 mg/kg/day). Differences were detected in EPA metabolites without a significant increase in plasma DHA.